Cultural and Linguistic Adaptation of a Multimedia Colorectal Cancer Screening Decision Aid for Spanish Speaking Latinos - Ko, Linda K. (2013)
As the United States becomes more linguistically and culturally diverse, there is a need for effective health communication interventions that target diverse and most vulnerable populations. Latinos also have the lowest colorectal (CRC) screening rates of any ethnic group in the U.S. To address such disparities, health communication interventionists are often faced with the challenge to adapt existing interventions from English into Spanish in a way that retains essential elements of the original intervention while also addressing the linguistic needs and cultural perspectives of the target population. We describe the conceptual framework, context, rationale, methods, and findings of a formative research process used in creating a Spanish language version of an evidenced-based (English language) multimedia CRC screening decision aid. Our multi-step process included identification of essential elements of the existing intervention, literature review, assessment of the regional context and engagement of key stakeholders, and solicitation of direct input from target population. We integrated these findings in the creation of the new adapted intervention. We describe how we used this process to identify and integrate socio-cultural themes such as personalism (personalismo), familism (familismo), fear (miedo), embarrassment (verguenza), power distance (respeto), machismo, and trust (confianza) into the Spanish language decision aid.